Asas Al-Furuq Al-Fardiyah Menurut Golongan Darah Dalam Belajar: Suatu Analisis Psikopedagogis - Hafiz, Abdul; Walidin, Warul; Syabuddin; Mahmud, Salami (Yayasan Dharma Lentera Khatulistiwa (MALEWA), 2024)
This paper aims to reveal individual differences based on a child's blood type from a psychopedagogical perspective. This research uses a literature study approach from Toshitaka Nomi's book resulting in a research book entitled Touch My Heart which was then analyzed and linked to psychopedagogy. The results of this research show that children with blood type O are active, while children with blood type A are responsible, and Children with blood type B have soft hearts, and children with blood type AB don't like boundaries set by their parents. This research provides a wealth of knowledge for teachers to approach students in classes who have various types of characters and different blood type backgrounds